Molecular analysis of canine filaria and its wolbachia endosymbionts in domestic dogs collected from two animal university hospitals in Bangkok metropolitan region, Thailand - Hathaithip Satjawongvanit (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Canine filariasis is caused by several nematode species, such as Dirofilaria immitis, Dirofilaria repens, Brugia pahangi, Brugia malayi, and Acanthocheilonema reconditum. Zoonotic filariasis is one of the world’s neglected tropical diseases. Since 2000, the World Health Organization (WHO) has promoted a global filarial eradication program to eliminate filariasis by 2020. Apart from vector control strategies, the infection control of reservoir hosts is necessary for more effective filariasis control. In addition, many studies have reported that Wolbachia is necessary for the development, reproduction, and survival of the filarial nematode. Consequently, the use of antibiotics to kill Wolbachia in nematodes has now become an alternative strategy to control filariasis. Previously, a case of subconjunctival dirofilariasis caused by Dirofilaria spp. has been reported in a woman who resides in the center of Bangkok, Thailand. Therefore, our study aimed to principally demonstrate the presence of filarial nematodes and Wolbachia bacteria in blood collected from domestic dogs from the Bangkok Metropolitan Region, Thailand. A total of 57 blood samples from dogs with suspected dirofilariasis who had visited veterinary clinics in Bangkok were collected. The investigations for the presence of microfilaria were carried out by using both microscopic and molecular examinations. PCR was used as the molecular detection method for the filarial nematodes based on the COI and ITS1 regions. The demonstration of Wolbachia was performed using PCR to amplify the FtsZ gene. All positive samples by PCR were then cloned and sequenced. The results showed that the filarial nematodes were detected in 16 samples (28.07%) using microscopic examinations. The molecular detection of filarial species using COI-PCR revealed that 50 samples (87.72%) were positive; these consisted of 33 (57.89%), 13 (22.81%), and 4 (7.02%) samples for D. immitis, B. pahangi, and B. malayi, respectively. While the ITS1-PCR showed that 41 samples (71.93%) were positive—30 samples (52.63%) were identified as containing D. immitis and 11 samples (19.30%) were identified to have B. pahangi, whereas B. malayi was not detected. Forty-seven samples (82.45%) were positive for Wolbachia DNA and the phylogenetic tree of all positive Wolbachia was classified into the supergroup C clade. This study has established fundamental data on filariasis associated with Wolbachia infection in domestic dogs in the Bangkok Metropolitan Region. An extensive survey of dog blood samples would provide valuable epidemiologic data on potential zoonotic filariasis in Thailand. In addition, this information could be used for the future development of more effective prevention and control strategies for canine filariasis in Thailand.